2003
DOI: 10.1016/s0160-4120(02)00129-0
|View full text |Cite
|
Sign up to set email alerts
|

Iodine uptake by spinach (Spinacia oleracea L.) plants grown in solution culture: effects of iodine species and solution concentrations

Abstract: A hydroponic experiment was carried out to investigate the effects of iodine species and solution concentrations on iodine uptake by spinach (Spinacia oleracea L.). Five iodine concentrations (0, 1, 10, 50 and 100 AM) for iodate (IO 3 À ) and iodide (I À ) were used. Results show that higher concentrations of I À ( R 10 AM) had some detrimental effect on plant growth, while IO 3 À had little effect on the biomass production of spinach plants. Increases in iodine concentration in the growth solution significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
120
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(146 citation statements)
references
References 13 publications
19
120
2
5
Order By: Relevance
“…It has been shown that Se can be easily translocated from roots to shoots if plants are fed with selenate (Zayed et al, 1998). The DC values for Se obtained in this study are comparable to those reported by Zayed et al (1998), and the DC values for I are comparable to those we reported earlier in solution culture (Zhu et al, 2003). In this study the concentrations of Se and I in the growth solution were much higher than would be conventionally found in arable soils.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that Se can be easily translocated from roots to shoots if plants are fed with selenate (Zayed et al, 1998). The DC values for Se obtained in this study are comparable to those reported by Zayed et al (1998), and the DC values for I are comparable to those we reported earlier in solution culture (Zhu et al, 2003). In this study the concentrations of Se and I in the growth solution were much higher than would be conventionally found in arable soils.…”
Section: Discussionsupporting
confidence: 88%
“…No se considera al yodo como un elemento esencial para las plantas terrestres, aunque diversos estudios demostraron que estas absorben y acumulan yodo (Mackowiak y Grossl, 1999;Zhu et al, 2003). Esta aparente no esencialidad explica el porque el yodo no se contempla en los programas de…”
Section: Disponibilidad Del Yodo En Los Alimentosunclassified
“…Iodine is not considered as an essential element for terrestrial plants, although several studies showed that these absorb and accumulate iodine (Mackowiak and Grossl, 1999;Zhu et al, 2003). This apparent non-essentiality explains why iodine is not contemplated in mineral fertilization programs of crops, despite the fact that it has been shown that the contribution of inorganic iodine salts can increase stress tolerance in plants (Leyva et al, 2011;Gupta et al, 2015).…”
Section: Availability Of Iodine In Foodmentioning
confidence: 99%
“…Iodine (I) is readily taken up by plants if available [1], which is important to both agronomy and radioecology because, although I is not an essential element for plants, food crops are a major conduit for the entry of I to human foodchains. Stable I ( 127 I) is an essential trace element for humans whilst the radioisotopes 131 I and 129 I can be significant radioactive contaminants of the environment [2].…”
Section: Introductionmentioning
confidence: 99%
“…In many soils I − and IO3 − are the most common ionic forms, with I − most likely to be taken up by plants [1] because they have substantial capacity for the uptake of the chemically similar Cl − [9]. Overall, although soil-to-plant transfer factors can be quite low from, for example, Andosols with high anion exchange capacities [10], hydroponic experiments show that plants can take up large quantities of I if it is available to them [1] and most soils produce transfers to crops that can contribute significantly to food I content and to radiocontamination if 127 I or 131/129 I are available in the soil.…”
Section: Introductionmentioning
confidence: 99%